2019
DOI: 10.1016/j.envsci.2018.11.010
|View full text |Cite
|
Sign up to set email alerts
|

Mustering the power of ecosystems for adaptation to climate change

Abstract: Mountain social-ecological systems (SES) supply important ecosystem services that are threatened by climate change. In mountain SES there is a paradox between high community capacity to cope with extremes, and governance structures and processes that constrain that capacity from being realised.Climate adaptation maintaining livelihoods and supply of ecosystem services can catalyse this innate adaptive capacity if new adaptive governance arrangements can be created. Using the French Alps as a case study, we out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 59 publications
3
57
0
3
Order By: Relevance
“…An analysis of responses to a survey of adaptation practitioners in Australia by Palutikof et al (2019) identified lack of leadership, knowledge and community support as the three main barriers to action. These correspond broadly to the three common prerequisites identified for transformational change to take place (knowledge, institutional alignment, stakeholder values) (Lavorel et al 2019), and to the values -rules -knowledge framing of Gorddard et al (2016), indicating how fundamental they are in blocking the shift from observed adaptation progress to the transformations required to address current rates of climate change. This abstract analysis makes clear that, despite whatever barriers exist, reportable adaptation action is taking place in Australia, and although it still represents a small proportion of adaptation activity (compared, for example, to planning), that proportion is growing over time.…”
Section: Discussionsupporting
confidence: 57%
“…An analysis of responses to a survey of adaptation practitioners in Australia by Palutikof et al (2019) identified lack of leadership, knowledge and community support as the three main barriers to action. These correspond broadly to the three common prerequisites identified for transformational change to take place (knowledge, institutional alignment, stakeholder values) (Lavorel et al 2019), and to the values -rules -knowledge framing of Gorddard et al (2016), indicating how fundamental they are in blocking the shift from observed adaptation progress to the transformations required to address current rates of climate change. This abstract analysis makes clear that, despite whatever barriers exist, reportable adaptation action is taking place in Australia, and although it still represents a small proportion of adaptation activity (compared, for example, to planning), that proportion is growing over time.…”
Section: Discussionsupporting
confidence: 57%
“…algae-dominated reefs after mass coral mortality [93]). However, sometimes new communities will provide similar adaptation benefits to the pre-disturbance communities and/ or provide additional novel adaptation services [94,95]. Further royalsocietypublishing.org/journal/rstb Phil.…”
Section: Effectiveness Of Nature-based Solutions Under Climate Changementioning
confidence: 99%
“…Grey infrastructural approaches are deeply engrained in certain cultural contexts, and shape institutional practices. Such biases are compounded by cognitive factors such as a lack of awareness of ecosystem services provided by NbS, lack of perceived responsibility for action or the discounting of climate risks [123,137,138] and similar issues that constrain innovation [95]. Overcoming these challenges requires strong institutions, and well-established planning structures, processes and instruments to ensure benefits across landscapes and seascapes [127,134].…”
Section: (B) Challenges To Governing Nature-based Solutionsmentioning
confidence: 99%
“…This definition is consistent with the ES concept, but additionally includes ecological mechanisms that support ecosystem persistence or transformation and focuses on developing, evaluating and implementing options for adaptation [19]. Different AS are mobilized sequentially or cumulatively along adaptation pathways: ecological resilience, latent and sustained ES are essential in early stages of adaptation while the use and values of ecosystem transformability and novel ES build up as environmental changes intensify [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…For example, throughout Africa, rangeland invasion by exotic Prosopis trees stabilizes soils and supports new activities of fuelwood charcoal collection [17]. Based on whether they are supported by ecosystems that persist or transform under climate change, and how their benefits are realized to reduce risks to livelihoods by creating new options, AS can be recognized as five types [18] (figure 1): (i) ecological resilience properties that support the persistence of current ecosystems and their services and (ii) their latent ES whose value is revealed for social adaptation (e.g. for mitigating new risks like storm surges or flash floods); (iii) ecological properties that underpin ecosystem transformability (e.g.…”
Section: Introductionmentioning
confidence: 99%